Kleine Levine Syndrome comorbid with obsessive compulsive disorder and personality disorder, A Case Report - Pezhman Hadinezhad; Javad Setareh; Parisa Adimi naghan (Babol University of Medical Sciences, 2023)
Background: Kleine-Levin syndrome (KLS) is a rare sleep disorder with at least two episodes of hypersomnia coincidence with at least one cognitive, eating, perceptive and disinhibited symptoms and normal inter-episodes. These symptoms are not explained by another sleep, medical, neurological, psychiatric disorders and substance or drug use. Case Presentation: Here we report a young female with personality disorder and obsessive-compulsive disorder who had KLS. Her symptoms appeared in the past 1.5 years ago, while she had an episode of hypersomnia lasting for 5 days. She had 4 attacks; each one lasted up to 2-7 days. We found that overriding KLS symptoms on underlying main psychiatric or personality disorders complicates diagnosis. All neurological examinations during episode and further investigation were in normal range. Conclusion: We suggest that taking a complete history and mental state examination in the episode and inter episode phase helps to diagnosis both KLS and comorbid psychiatric disorders.